Examining the progress and implementation of neonatal peritoneal dialysis in the Ningxia autonomous region - Zhen Tian; Xiu Luo; Hua Yang; Zhi-Mei Ma; Juan Yang; Yong-Jia Ji (BMC Pediatrics)
Abstract Background Neonates are prone to experiencing acute kidney injury (AKI) and metabolic irregularities. Although hemodialysis is a primary treatment for these conditions, its utilization is not prevalent in the Ningxia Autonomous Region in China. Peritoneal dialysis (PD) presents itself as an alternative with benefits such as simplicity, cost-effectiveness, and minimal technical complexity compared to hemodialysis. Nonetheless, the safety and efficacy of employing PD in neonates, particularly in very low birth weight infants, require additional investigation. Objective In this study, we explored the practical use of PD in neonates in the region of Ningxia. Methods The retrospective analysis focused on the clinical information of neonates undergoing PD at the neonatal intensive care unit of PKUFH-NINGXIA Women & Children’s Hospital, covering the period from January 2021 to August 2023. Results A total of 7 neonates (3 males and 4 females) were included in the study, including one early preterm infant (28–31+ 6 weeks’ gestational age), one moderately preterm infant (32–33+ 6 weeks’ gestational age), two late preterm infants (34–36+ 6 weeks’ gestational age), and three term infants. The minimum gestational age recorded was 28 + 6 weeks and the lowest body weight was 1,075 g. Among the cases, sepsis was the primary cause of AKI in three cases (43%), with preterm infants accounting for 67% of these cases; genetic metabolic disorder in two cases (28.5%), and twin-twin transfusion syndrome in two cases (28.5%), both involving premature infants; and one of these two involving severe asphyxia. The onset of dialysis occurred between 1 and 24 days of age, and the duration of dialysis ranged from 1 to 5 days. The dialysis procedures for all seven cases were executed smoothly, and there were no complications observed in terms of unsecured catheter leakage at the insertion site, hyperglycemia, hypokalemia, catheter occlusion, peritonitis, or catheter detachment during the peritoneal dialysis treatment. Conclusion The use of peritoneal dialysis proves to be a safe and efficient approach in addressing neonatal AKI.